2019
DOI: 10.1097/acm.0000000000003117
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Medical Malpractice Claims Involving Physician Trainees

Abstract: Additional information on variables Loss date was the date on which the harm occurred, not when it was discovered. Filing time was the difference between when the loss occurred, and a claim was filed. Open claim time was the difference between when a claim was filed and the claim closed. Primary responsible provider was the specialty of the provider whom the coder felt was responsible for the harm event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Overall, general surgery had higher risk of malpractice when compared with other surgical subspecialties, 18 54 however, agreement was not universal. 55 Grey literature and published academic papers reported GPs and family medicine specialists comprise a large proportion of total claims (34%–62%) and were up to three times as likely to be subject to claims. 33 50 55 56 Other high-risk specialties include psychiatry, obstetrics and gynaecology, which were noted to be between four and 17 times as likely to be subject to malpractice claims compared with GPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, general surgery had higher risk of malpractice when compared with other surgical subspecialties, 18 54 however, agreement was not universal. 55 Grey literature and published academic papers reported GPs and family medicine specialists comprise a large proportion of total claims (34%–62%) and were up to three times as likely to be subject to claims. 33 50 55 56 Other high-risk specialties include psychiatry, obstetrics and gynaecology, which were noted to be between four and 17 times as likely to be subject to malpractice claims compared with GPs.…”
Section: Resultsmentioning
confidence: 99%
“… 39 51 60 61 64 In contrast, three studies reported practitioners with fewer years in practice had higher odds of a malpractice claim or medical litigation. 55 65 66 …”
Section: Resultsmentioning
confidence: 99%
“…There is robust quality assurance, including biweekly coder conference calls, annual conferences, and auditing processes where 15% of claims are reviewed quarterly. Previous scholarly work has been published using these data 9–12 …”
Section: Methodsmentioning
confidence: 99%
“…There is robust quality assurance, including biweekly coder conference calls, annual conferences, and auditing processes whereby 15% of the claims are reviewed quarterly. Several studies have been published using the database 15‐18 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been published using the database. [15][16][17][18] The Institutional Review Board provided an exemption (2019P001490).…”
Section: E T H O D S Study Design and Data Sourcementioning
confidence: 99%